A Case Report of a Combined Bypass Surgery on Coronary Artery and Right Common Femoral Artery of the Aorta - Halici, Umit; Vali, Riza; Yasar, Birkan; Ozbudak, Ersan; Kanca, Atilla; Sanioglu, Soner (Annals of Medical Research, 2021)
None